(untitled) (Tanzania Journal for Population studies and Development, 2021)
This article presents socio-economic implications of protracted refugees on peace and security in Tanzania as informed by the experiences unveiled from a study conducted at Nyarugusu Refugee Camp in Kigoma Region. It is a product of a case study research design of a sample of 79 respondents obtained through systematic and purposive sampling. The sample was drawn from refugees in Nyarugusu Camp, community members, refugee’s leaders, UNHCR personnel and local government authority leaders. Data was collected through questionnaires, in-depth interviews, focus group discussions and observation. Data was analysed qualitatively and quantitatively. Quantitative data was analysed using descriptive statistics, while qualitative data was analysed using content analysis. The findings revealed that refugees in Tanzania have been staying in camps for many years, thus creating threat and insecurity to the host community. The host community also faces parallel impacts in relation to security of their properties, disharmony, immoral behaviour such as rape, armed robbery, congestion in social services; and loss of land without direct compensation. Also, the host communities were affected in their daily activities such as agriculture and businesses, as well as access to social services which they had to share with refugees. The study recommends that the national refugee policy document be reviewed to lessen its implementation challenges and accommodate all categories of refugees; the government plan ahead possible refugee influx and measures to attend them; the government and development partners carry more research on refugees’ life in camps to find out possible solutions to refugees case load; and subsequently devise durable solutions to the problem of prolonged refugees in the country.